Delirium and Associated Length of Stay and Costs in Critically Ill Patients. (24th April 2021) - Dziegielewski, Claudia; Skead, Charlenn; Canturk, Toros; Webber, Colleen; Fernando, Shannon M.; Thompson, Laura H.; Foster, Madison; Ristovic, Vanja; Lawlor, Peter G.; Chaudhuri, Dipayan; Dave, Chintan; Herritt, Brent; et al.
Abstract : Purpose . Delirium frequently affects critically ill patients in the intensive care unit (ICU). The purpose of this study is to evaluate the impact of delirium on ICU and hospital length of stay (LOS) and perform a cost analysis. Materials and Methods . Prospective studies and randomized controlled trials of patients in the ICU with delirium published between January 1, 2015, and December 31, 2020, were evaluated. Outcome variables including ICU and hospital LOS were obtained, and ICU and hospital costs were derived from the respective LOS. Results . Forty-one studies met inclusion criteria. The mean difference of ICU LOS between patients with and without delirium was significant at 4.77 days (p < 0.001 ); for hospital LOS, this was significant at 6.67 days (p < 0.001 ). Cost data were extractable for 27 studies in which both ICU and hospital LOS were available. The mean difference of ICU costs between patients with and without delirium was significant at 3, 921 (p < 0.001 ); for hospital costs, the mean difference was 5, 936 (p < 0.001 ). Conclusion . ICU and hospital LOS and associated costs were significantly higher for patients with delirium, compared to those without delirium. Further research is necessary to elucidate other determinants of increased costs and cost-reducing strategies for critically ill patients with delirium. This can provide insight into the required resources for the prevention of delirium, which may contribute to decreasing healthcare expenditure while optimizing the quality of care.